Issues : the cross-curricular course for PSE - Foster, John Same author(5) (London : CollinsEducational. 1993., 2010)
These teacher's resources accompany the fourth book in a PSE course for pupils of all abilities at Key Stages 3 and 4. The series is designed for use on a year-by-year basis, but the structure is flexible enough to allow teachers to use the sections selectively.
Keywords: Social sciences -- Study and teaching (Secondary) Social sciences -- Curricula. Schools -- Curriculum